Medieval architecture of the Dominican church in Opole (the so-called “na Górce”) and its transformations from the end of the 13th century to the beginning of the 18th century - Lasota, Czesław; Legendziewicz, Andrzej (Średniowieczna architektura kościoła dominikańskiego w Opolu (tzw. na Górce) i jej przekształcenia od schyłku XIII w. do początku XVIII w., 2022)
The article concerns the transformations of the architecture of the Dominican church of Our Lady of Sorrows and St. Wojciech (the so-called “na Górce”) in Opole. The paper presents the results of original architectural research conducted from 2008 to 2017. Previous analyses regarding the construction and transformation of the church “na Górce” are based on the findings of pre-war researchers, which relied on a general inspection of the plastered building. The discussed architectural research enabled the scope of the original monastic church, and its expansion from around 1361, to be distinguished. This also applies to the enlargement of the chancel and its adaptation, as well as to the construction of a two-nave, four-bay nave. The chancel of this church was enlarged in around 1399 by adding a polygonal eastern closure, and the church itself was probably renovated and enlarged in around 1430 by the construction of an outbuilding adjacent to the nave. The presented research results significantly change the previously published description concerning the construction and transformation of the architecture of the Dominican church in Opole.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 37-46
Keywords: architektura; Silesia; architecture; Middle Ages; church; Dominicans; Opole; Śląsk; średniowiecze; kościół; dominikanie